GUIDING NOBLE MORALS BASED ON AYYUHAL WALADUL MUHIBBAH BY AL GHAZALI WITH THE TAZKIYATUN NAFS APPROACH - Dina Susanti (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2020)
The crisis of noble character in this technological era is increasing, it is marked by increasing juvenile delinquency. Santri who are far from their parents are also of particular concern in this article, because the formation of the noble character is very much needed by the students, this is the background of this article. Guiding noble character to students is very important to do. The method in this article research is by library research, Field Research and FGD to several senior coaches with interview, observation and documentation data collection techniques, and using data analysis and source Triangulation techniques. The results of this study are the formation of Santri's Noble Character with the Tazkiyatun Nafs approach according to Imam Ghazali in the Ayyuhal Waladul Muhibbah. The Purpose, The Material (Self Concept as khalifatullah and Abdullah, Moral to God, Moral to Teachers and Parents, Moral in association) the Method namely Direct Method consists of: 1) Personal: Coaching and Counseling and Muhasabah, and 2). Groups: Lectures, Repentance Activities, Dhikr & Prayer Activities, Stories and Muhasabah. Indirect Method: Modeling, Customizing and Supervising. Evaluation consists of evaluation materials, namely 1). Worship, 2). Noble character. Morals with friends and Morals with the environment. And Evaluation Methods: Observation, Practice and 360˚ evaluationABSTRAKKrisis karakter mulia dalam era tekhnologi ini semakin meningkat, hal tersebut di tandai dengan meningkatnya kenakalan remaja. Santri yang jauh dari kedua orangtua nya juga menjadi perhatian khusus dalam artikel ini, karena pembinaan karakter mulia sangat di butuhan oleh para santri, hal ini menjadi latar belakang artikel ini. Pembinaan karakter mulia kepada santri merupakan hal yang sangat penting di lakukan. Metode dalam penelitian artikel ini adalah dengan library research, Field Reseach dan FGD kepada beberapa Pembina senior dengan tehnik pengumpulan data wawancara, observasi dan dokumentasi, serta menggunakan analisis data Triangulasi sumber dan Tehnik. Hasil dari penelitian ini adalah Pembinaan Karakter Mulia (Mentoring) Santri dengan pendekatan Tazkiyatun Nafs Menurut Imam Ghazali dalam kitab Ayyuhal Waladul Muhibbah. Tujuan Kokurikulum, Materi Kokurikulum (Konsep Diri sebagai khalifatullah dan Abdullah, Akhlak kepada Allah, Akhlak Kepada Guru dan orangtua , Akhlak dalam pergaulan ) Metode Kokurikulum yaitu Metode Langsung terdiri dari : 1) Personal : Coaching and Counseling dan Muhasabah, dan 2). Kelompok : Ceramah, Aktivitas Taubat , Aktivitas Dzikir & doa, Kisah dan Muhasabah. Metode tidak langsung: Keteladanan , Pembiasaan dan Pengawasan. Evaluasi Kokurikulum terdiri Materi Evaluasi yaitu 1). Ibadah, 2). Karakter mulia. Akhlak terhadap teman dan Akhlak terhadap lingkungan. Dan Metode Evaluasi : Observasi , Praktek dan 360˚ evaluasi